Probing into the Influence of Web Based and Mobile based Instruction on Vocabulary Learning; Lexical Depth and Breadth in Focus - Ghobadi, Tabasom; Nourbakhsh, Atin (LANGUAGE ART, 2024)
This study investigated the effects of web-based and mobile-assisted instruction on Iranian EFL learners’ lexical depth and breadth. Out of 150 learners, 120 intermediate participants were selected through an Oxford Placement Test and randomly assigned to three equal groups: one receiving web-based instruction, one taught through Mobile-Assisted Language Learning (MALL), and a control group receiving traditional instruction. Prior to the treatment, a vocabulary pretest was administered to all groups. The instructional intervention lasted for eight sessions, during which the web-based group used online vocabulary learning programs and the MALL group received instruction via a mobile application. The control group was taught through conventional classroom methods. A posttest was then administered to measure the impact of the treatments. Data were analyzed using ANCOVA. The findings revealed that both web-based and mobile-assisted instruction significantly enhanced learners’ lexical depth and breadth compared with the traditional method. Moreover, no statistically significant difference was observed between the effects of the two technology-enhanced instructional modes. Pedagogical and theoretical implications are discussed.